The Implementation of Accounting Information Systems for its Role in Marketing and Management Processes (European Journal of Marketing and Economics, 2023)
Nowdays the technological innovations evolve faster and in this conditions it is necessary to examine how this technology affects the accounting profession in the same way as it has affected everyday aspects. Accounting is transformed into something more than simple recording, summarizing and reporting of transactions exceeding these routines and practical functions and extending throughout the organization including, delegated functions, processing methodologies, controls and expected outputs, which considered all together as "the system ". It includes all dimensions of business operations, including the flow of financial data across the organization and beyond. Consequently, this paper aims to address issues such as how knowledge about IT deal from accounting professionals and how they further develop their professional development during the subsequent training. This paper shows the importance of the IT knowledge in accounting, marketing, management and decision making. We conclude the paper by giving a short overview relying on the analysis of data collected from a survey.
Keywords: information technology, accounting information system, management, marketing